Assessing the economic content of direct and indirect business uncertainty measures - Christian Glocker; Werner Hölzl (Austrian Institute of Economic Research (WIFO), 2019)
We introduce a novel measure of uncertainty that is based on a business survey in which firms are asked directly how certain or uncertain they are. So far the literature has tried to capture economic uncertainty indirectly by means of expectation errors or the extent of disagreement. Our direct measure of economic uncertainty has a decent contemporaneous correlation with various indirect measures, its informational content is though different. Across all uncertainty measures, shocks to uncertainty trigger effects in GDP of opposite sign, however, the indirect measures tend to significantly underestimate the effects on GDP and other macroeconomic aggregates.
Keywords: E32; E37; E44; C80; 330; Uncertainty shocks; Aggregate fluctuations; Firm dispersion; Surveys of expectations